INTRODUCING THARIQAH AKADEMIK TO AR-RASYID PUPILS TOWARD GOLDEN INDONESIA 2045 (International Conference on Social and Islamic Studies, 2021)
On the road to Golden Indonesia in 2045, we must prepare to acquire the skills of the younger generation. Thariqah Akademik is a prototype for harnessing knowledge, skills, and attitudes through basic activities centered around three major programs. First, it promotes human knowledge in five major subjects: math, English proficiency, Arabic proficiency, and the Qur'an memorization and writing skill. The second is to sharpen our spiritual sense through religious activities, specially accustomed to Shalat Hajat. Third, environmental protection is promoted by leading them to a healthy life and promoting the conservation of society and nature in a balanced manner. The study was conducted in a qualitative way to get an accurate picture of what was happening around the subject. This study intentionally chose both observation and interview as the tool and means of this research. The findings are mentioned as a shown list below: 1. Changes in students' opinions about the future, 2. Building ideas to deepen understanding of the above majors. 3. focus on the country's priority areas and catching opportunities for future prospects.